IMPLEMENTATION OF THE BEST INTERESTS PRINCIPLE FOR CHILDREN WHO COMMIT VIOLENT CRIMES RESULTING IN THE DEATH OF CHILDREN (STUDY IN THE CENTRAL JAKARTA DISTRICT COURT) - Amin, Rahman; Al Aziz, Muh. Fikri (Jurnal Bina Mulia Hukum, 2023)
Children are the future generations of the nation and state, and it is essential that they receive protection to ensure their growth into fully developed human beings. However, in today's society, many children become entangled with the law, go through legal processes, and even face criminal sentences, where the principle of the best interests of the child is not yet the primary consideration for law enforcement authorities in handling cases involving children. This situation can have negative effects on a child's development. This study is a normative-empirical legal research with a legislative and case-based approach. The research findings indicate that the implementation of the best interests principle for children who commit violent crimes resulting in the death of children (a study conducted in the Central Jakarta District Court) is not yet optimally realized. During the legal proceedings, investigators and prosecutors still detain children, imprisonment remains the prosecutor's choice in the indictment, and during the trial, judges still opt for primary imprisonment as a punishment, even though there are alternative forms of sanctions such as rehabilitation, either within or outside institutions, which could be imposed on children, considering the conditions they are currently experiencing for their future well-being and development.